Modified Pedicle Subtraction Osteotomy for Posttraumatic Kyphosis: Long Term Follow-Up - Ahmed Sleem (Egyptian Spine Association, 2017)
its management can be quite challenging. Pedicle subtraction osteotomy includes posteriorly based wedge resection of the posterior column and both pedicles, with the hinge located at the anterior cortex of the vertebral body. It has been developed to achieve significant deformity correction. It does not involve the adjacent disc which is usually affected and represents a cause of pain, neurological compression and progression of deformity. Modified pedicle subtraction osteotomy (MPSO) including resection of posteriorly based wedge of posterior column and both pedicles together with the damaged disc to achieve correction and solid fusion between the affected vertebra and the adjacent one. It seems to be more suitable for the management of PTK. Purpose: The purpose of this prospective study is to review our experience with modified Pedicle subtraction osteotomy (MPSO) technique for the management of thoracolumbar posttraumatic kyphosis (PTK). Study Design: Prospective cohort clinical case study. Patients and Methods: From February 2010 to July 2014, 14 consecutive patients with PTK were managed by MPSO. The patients were followed clinically and radiologically. Back pain VAS, Denis work scale and regional kyphotic angle (RKA) were recorded and analyzed preoperatively, postoperative and at the latest follow up. Results: The study included 14 patients with an average age of 38.43±6.63 (26 - 48) years. The follow up period was 46.29±15.45 months. The average operative time was 286.43±12.74 minutes and per-operative blood loss was 1017.86±198.75 ml. Back pain VAS improved from 8.21±0.77 preoperatively to 2.50±0.73 at the last follow-up (P=0.034), and the Denis work scale improved from 4.43±0.49 preoperatively to 1.64±1.23 at the last follow-up (P=0.022). Neurological improvement occurred in one patient from ASIA grade D to E with no postoperative deterioration in any case. The regional kyphotic angle (RKA) significantly improved from 42.07±5.28° preoperatively to 2.67±2.58° after surgery (P=0.04) with a mean correction of 38.47±5.42°. The loss of correction was 1.92±0.73° at the latest follow-up. The complications included 2 dural tears and 3 postoperative wound infections. Conclusion: MPSO technique provides significant correction of patient’s kyphosis with a risk profile similar to a standard PSO procedure. (2016ESJ122)